Game Edukasi Interaktif Pengenalan Tata Surya Berbasis Animasi 2D untuk Siswa Kelas 6 SD - Nur Budi Nugraha (STEKOM PRESS, 2022)
The solar system is one of the natural science lessons taught in grade 6 elementary school. This material is abstract because in studying it children cannot directly observe the phenomena of celestial bodies in the solar system. So far, only using books or 2D images as media. This study aims to create an educational game about the introduction of the solar system. 2D animation is made with icons and audio so that it can attract students' interest in learning and remembering solar system material. The result of the research is an educational game as an effective means of entertainment and learning. Students become interested in learning because of the application of the dissertation with attractive images and audio that helps increase enthusiasm for learning about the solar system. In testing the respondents as many as 22 people, the calculation results obtained as much as 59.1% strongly agree with this educational game